Cooperation in a generalized age-structured spatial game. (7th January 2020) - Souza, Paulo Victor Santos; Silva, Rafael; Bauch, Chris; Girardi, Daniel
Highlights: In an age-structured spatial PD game, cooperators can survive and even dominate the population when a Gaussian distribution is used to normalize the payoffs according to the age of the agents. The Gaussian renormalization promotes the cooperation independent of which age the distribution is centered ( apriv ) but only for a range of Gaussian standard deviation. The standard deviation and the maximum value of temptation to defect where the individuals still cooperate are obtained as a function of apriv . Clusters of agents who share the same strategy are formed around the agent whose age is privileged in the game. If apriv is smaller than average life expectancy the maximum of temptation is constant. For apriv greater than average life expectancy the temptation is a decreasing linear function of apriv . Abstract: The emergence and prevalence of cooperative behavior within a group of selfish individuals remains a puzzle for evolutionary game theory precisely because it conflicts directly with the central idea of natural selection. Accordingly, in recent years, the search for an understanding of how cooperation can be stimulated, even when it conflicts with individual interest, has intensified. We investigate the emergence of cooperation in an age-structured evolutionary spatial game. In it, players age with time and the payoff that they receive after each round depends on their age. We find that the outcome of the game is strongly influenced by the type of distribution used to modify the payoffs according to the age of each player. The results show that, under certain circumstances, cooperators may not only survive but dominate the population.